Discovering the Contrasts between Augmented Reality and Virtual Reality in Teaching University Courses - Mutaz Mohammed Abuhashish; Leyla Muradkhanli (Research Parks Publishing LLC, 2023)
Augmented Reality (AR) and Virtual Reality (VR) are two developing technologies with enormous promise to change the way education is provided. The purpose of this research is to investigate the fundamental distinctions between AR and VR in the context of course instruction. Educators can acquire insights into how these technologies might be effectively integrated into the classroom by evaluating their specific traits, affordances, and limits. The research begins by defining AR and VR and then compares their key ideas. AR superimposes digital information on the real-world environment to improve the user's impression of reality, whereas VR immerses users in a simulated environment to create a sensation of presence and immersion. These contrasts lay the groundwork for comprehending their disparate uses in education. The study then goes into the educational benefits and difficulties of AR and VR. AR allows students to interact with digital information in real time, encouraging engagement, collaboration, and contextualized learning. It could bridge the gap between abstract ideas and real-world applications. VR, on the other hand, provides an immersive and regulated environment that allows students to explore complicated scenarios, imitate real-world circumstances, and acquire important skills in a safe and cost-effective manner. The research looks at the technology needs, accessibility concerns, and implementation techniques for AR and VR in educational settings. It emphasizes the significance of pedagogical design, content creation, and teacher training to maximize these technologies' educational impact. This review paper investigates the differences between Augmented Reality (AR) and Virtual Reality (VR) in the context of course education. AR and VR have emerged as significant tools for boosting the learning experience as technology continues to alter education. Understanding the distinct characteristics and benefits of each technology is critical for educators to make educated judgments about how to include them in their teaching practices. This paper examines AR and VR in depth, concentrating on their distinctions, uses, and possible influence in educational contexts.